Efficacy of doxycycline as a combination therapy in the treatment of rheumatoid arthritis: a randomized controlled clinical trial - Eman M. Ibrahem; Salwa S. El-gendi; Amal A. Mahmoud; Sherif M. Abdel-Aal; Hanan Sharaf El-Deen Mohammed (SpringerOpen, 2021)
Abstract Background This single-center randomized open-label clinical trial evaluates the effectiveness of doxycycline as a combination therapy for active rheumatoid arthritis (RA) with methotrexate (MTX). Materials and methods One hundred and sixty RA patients were recruited who fulfilled the 2010 American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) classification criteria. Subjects were randomly allocated in a 1:1 ratio into one of two treatment arms; one group was maintained on MTX alone and the other group on MTX together with doxycycline orally 200 mg daily. Follow-up clinical response, erythrocyte sedimentation rate (ESR), levels of C-reactive protein (CRP), and disease activity score 28 (DAS28-CRP) after 3 months were done. Results There was a significant difference regarding DAS28-CRP between the two groups (median (IQR) 4.26 (3.6-5) for those treated with MTX alone compared with 2.8 (2.37-3.5) for those treated with MTX together with doxycycline) (p = 0.005). A higher number of patients treated with doxycycline in combination with MTX achieved remission (40.5%) compared to patients who received MTX alone (13.5%). The levels of ESR and CRP were lower in patients treated with MTX and doxycycline and this was statistically significant (p = 0.005, p = 0.003 respectively). Conclusion Doxycycline as a cost-effective combination therapy with MTX can achieve higher rates of remission than MTX alone in RA patients without causing increase in the adverse events profile. Trial registration Clinical Trials.gov, NCT03194204 . Registered on 21 June 2017